On the Measurement of Spontaneous Platelet Aggregation. The Platelet Aggregation Test III. - Breddin, K; Grun, H; Krzywanek, H. J; Schremmer, W. P (Thrombosis and Haemostasis, 1976)
A new measuring device was developed for the study of “spontaneous” aggregating activity of thrombocytes. In the photometric platelet aggregation test (PAT III) 0.6 ml of platelet-rich plasma (PRP) are rotated in a disc-shaped cuvette at 20 rpm and 37° C. Changes in optical density of PRP which are induced by the formation of platelet aggregates are continuously registered using a chart recorder. PAT III was developed for the detection of enhanced platelet aggregation, indicating a risk of thrombosis and thromboembolic complications.In 146 healthy individuals a certain percentage showed slight primary aggregation (α1) which in some cases was followed by marked aggregation (α2) at a certain time (Tr) after the beginning of rotation. The percentage of individuals showing α2 increased with age. An increase of plasma pH in the rotating sample, which was caused by diffusion of CO2, was an important conditioning factor for aggregation. The test results depended on the platelet count in PRP. Aggregation curves were suppressed by admixture of erythrocytes and lipid turbidity. The tendency of platelets to aggregate increased within 60–90 min following blood sampling. During this period the interval to the onset of aggregation (Tr) became shorter and the maximum aggregation speed (α2) increased with time. PAT III yielded reproducible results when it was carried out more than 60 min after blood drawing.In a group of 327 diabetic patients “spontaneous” aggregation occurred more frequently in all age groups as compared with the controls.Additional equipment was available for the registration of ADP-, collagen-, or epine-phrine-induced aggregation similar to Born’s and O’Brien’s method. The device can easily be mounted on an Eppendorf photometer without further alterations.